A critical control points based approach for reduction of mastitis incidence in dairy farms of Karnataka - DEVI, LETHA G; ADBHAI, AMOL D; KATAKTALWARE, MUKUND A; MECH, A; PAL, D T; GIRIDHAR, K; ARANGASAMY, A; SENANI, S; NIKETHA, L (The Indian Journal of Animal Sciences, 2020)
Hazard analysis critical control points (HACCP) based system is mainly a risk based preventive approach developed to increase food safety assurance level from farm. This program deals with control factors affecting the process and product. A semi-structured questionnaire was administered to 101 farmers in the adopted villages, covering 134 crossbred dairy cows. The baseline data indicated that based on California Mastitis Test (CMT) the incidence of clinical and subclinical mastitis in crossbred cow was 8.21 and 44.78% respectively. The risk factors associated with the incidence of mastitis were parity, level of milk yield, udder hygiene, udder shape, teat length, teat-tip-to-ground distance, animal housing conditions, milking management, post-milking time taken by the animal for lying down, a long gap in tail hair clipping. CCPs identified and developed plan may be suitable for customized and implementation on small-holder dairy farms. This is a logical, effective and systemic approach for control of incidence of mastitis, improve the udder health status and milk quality.